2009
DOI: 10.1177/147323000903700216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alendronate on the Proliferation and Osteogenic Differentiation of MG-63 Cells

Abstract: Previous studies of the direct actions of bisphosphonates on bone have mainly been limited to their effects on bone-resorbing osteoclasts and little is known about the direct effects of bisphosphonates on osteoblasts. Here we report the direct effects of alendronate on the proliferation and osteogenic differentiation of the MG-63 osteoblast-like cell line. Cell proliferation was determined with the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay, osteogenic differentiation was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
45
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 26 publications
10
45
0
6
Order By: Relevance
“…These results are consistent with previous in vitro findings that BPs exert a pro-osteoblastogenic effect at lower concentrations (10 −5 to 10 −9 M) but an inhibitory effect at higher concentrations [34][35][36][37]. In common with previous reports, the present results suggest that BPs exert a beneficial effect on the osteoblast by enhancing its proliferative capacity, although account should be taken of the inverse dose-rate effect observed at the assayed doses.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are consistent with previous in vitro findings that BPs exert a pro-osteoblastogenic effect at lower concentrations (10 −5 to 10 −9 M) but an inhibitory effect at higher concentrations [34][35][36][37]. In common with previous reports, the present results suggest that BPs exert a beneficial effect on the osteoblast by enhancing its proliferative capacity, although account should be taken of the inverse dose-rate effect observed at the assayed doses.…”
Section: Discussionsupporting
confidence: 95%
“…The effects of BPs on this differentiation and maturation process are controversial, with some studies finding that BPs reduce ALP synthesis [38] and others suggesting that low doses of nitrogen-containing BPs increase ALP activity and nodule formation. In the present study, low doses of BPs reduced ALP activity and nodule formation [34,35,39], indicating an inhibitory effect on the differentiation and maturation of the osteoblast as bone-forming cell.…”
Section: Discussionmentioning
confidence: 85%
“…CPAH, in particular, appeared to induce greater proliferation than CP and CPAL during 3 and 5 d. This result elucidates that ALN incorporated at the concentration of 10 À4 M was effective for the promotion of MG63 cell proliferation. Previous studies reported that ALN can induce OB proliferation [14,24]. The current study confirmed that its biological activity was effectively maintained even after ALN was incorporated in CP [14,24].…”
Section: Resultssupporting
confidence: 92%
“…Previous studies reported that ALN can induce OB proliferation [14,24]. The current study confirmed that its biological activity was effectively maintained even after ALN was incorporated in CP [14,24]. The morphological images of the adherent MG63 cells were taken after culturing 7 d on sample films and shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…The chemical properties of these compounds cause them to be retained in the mineral phase of the bone, but whether this affects the organic composition is not known. Bisphosphonates do affect the biosynthetic characteristics of osteoblasts 21,22 , suggesting that there may be alterations in the extracellular matrix as a consequence of use. Recently, it has been found that the addition of bisphosphonates to implanted allograft bone affects the rate of allograft resorption and can affect the success of implants used with allograft 23,24 .…”
mentioning
confidence: 99%